TANGGUNG JAWAB PEMILIK PERANGKAT ALAT ELEKTRONIK YANG DISALAH GUNAKAN UNTUK PROSTITUSI ONLINE (STUDI PUTUSAN NOMOR 65/PID.SUS/ 2023/PN.WNS): Responsibility Of The Owner Of Electronic Devices That Are Misused For Online Prostitution (Study Decision Number 65/Pid.Sus/ 2023/Pn.Wns) - Mochamad Erlano Senaji; Andi Widiatno (Jurnal Hukum PRIORIS, 2024)
The advancement of information technology has introduced new legal challenges, particularly in online prostitution cases. This study examines the criminal liability of electronic device owners used in online prostitution, focusing on the Court Decision Number 65/Pid.Sus/2023/PN.Wns. The defendant, JF, was charged under Article 27 Paragraph (1) in conjunction with Article 45 of the ITE Law and Article 56 Paragraph (2) of the Indonesian Criminal Code for alleged assistance and transmission, despite only lending an electronic device without direct involvement in the crime. The analysis reveals that the defendant did not meet the elements of transmission or assistance and, therefore, should not be held criminally liable. The geen straf zonder schuld principle should apply, as no actual wrongdoing was proven. Thus, the court ruling is deemed inconsistent with justice and legal certainty. This study highlights the need for clearer regulations regarding the liability of electronic device owners in criminal law.